Glycosidase- and β-lactamase-like activity of dinuclear copper(II) patellamide complexes - Comba, Peter; Eisenschmidt, Annika; Kipper, Nora; Schießl, Jasmin (Journal of inorganic biochemistry, 2016)
Prochloron, a blue-green algae belonging to ancient prokaryotes, produces, like other cyanobacteria, cyclic pseudo-peptides, which are also found in its obligate symbiont ascidiae (Lissoclinum patellum). Although research has focused for some time on the putative metabolic function of these cyclic peptides, to date it is still not understood. Their role might be connected to the increased concentrations of divalent metal ions, especially CuII, found in ascidiae. Dinuclear copper(II) complexes of cyclic pseudo-peptides revealed a broad hydrolytic capacity, including carboanhydrase and phosphatase activity. This study reports their β-lactamase as well as α- and β-glycosidase activity with kcat=(11.34±0.91)ˑ10−4s−1 for β-lactamase, kcat=(1.55±0.13)ˑ10−4s−1 for α-glycosidase and kcat=(1.22±0.09)ˑ10−4s−1 for β-glycosidase activity.
Gesehen am 04.05.2020